Piperlonguminine a new mitochondrial aldehyde dehydrogenase activator protects the heart from ischemia/reperfusion injury - Yoval-Sánchez, Belem; Calleja, Luis Francisco; de la Luz Hernández-Esquivel, María; Rodríguez-Zavala, José Salud (Biochimica et biophysica acta. General subjects, 2020)
Detoxification of aldehydes by aldehyde dehydrogenases (ALDHs) is crucial to maintain cell function. In cardiovascular diseases, reactive oxygen species generated during ischemia/reperfusion events trigger lipoperoxidation, promoting cell accumulation of highly toxic lipid aldehydes compromising cardiac function. In this context, activation of ALDH2, may contribute to preservation of cell integrity by diminishing aldehydes content more efficiently. The theoretic interaction of piperlonguminine (PPLG) with ALDH2 was evaluated by docking analysis. Recombinant human ALDH2 was used to evaluate the effects of PPLG on the kinetics of the enzyme. The effects of PPLG were further investigated in a myocardial infarction model in rats, evaluating ALDHs activity, antioxidant enzymes, oxidative stress markers and mitochondrial function. PPLG increased the activity of recombinant human ALDH2 and protected the enzyme from inactivation by lipid aldehydes. Additionally, administration of this drug prevented the damage induced by ischemia/reperfusion in rats, restoring heart rate and blood pressure, which correlated with protection of ALDHs activity in the tissue, a lower content of lipid aldehydes, and the preservation of mitochondrial function. Activation of ALDH2 by piperlonguminine ameliorates cell damage generated in heart ischemia/reperfusion events, by decreasing lipid aldehydes concentration promoting cardioprotection. [Display omitted] •Binding of piperlonguminine activates ALDH2 and protects the enzyme from inactivation by lipid aldehydes.•Activation of ALDH2 avoids accumulation of toxic aldehydes protecting the heart.•ALDHs are feasible drug targets for the protection from ischemia-reperfusion events.•Administration of piperlonguminine may reduce the damage during myocardial infarction.